Hijab is Women’s Shield and Fortress - Hüseyin Çaksen (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Hijab has been applied in different forms in different civilizations and traditions since the era of first man and prophet Adam (Alayhi As-Salam). So, hijab and seclusion were practiced in many cultures long before Islam. Hijab is compulsory for women to save their modesty and chastity of all periods and times in Islam. Hijab themselves is natural for women and their innate dispositions demand it. Hijab frees women from being thought of as sexual objects of desire, or from being evaluated by their looks, or body shape rather than their minds and intellect. Studies indicate that girls and women may encounter sexual violence in their day-to-day social life in all cultures and societies. Hijab protects adolescent girls and women from sexual harassment. Hijab is women’s shield and fortress. The obvious fact is this, that the house is a protecting and secure place for a woman in a society. Islam does not like to go outside from the house without the essential needs. If the woman goes outside because of the essential requirement, then she should cover her whole body with a long cloth and should keep her gaze down. Allah says “And say to the believing women that they should lower their gaze and guard their modesty; that they should not display their beauty and ornaments except what (ordinarily) appear thereof; that they should draw their veils over their bosoms.